Li counterion-exchanged TEMPO-oxidized cellulose nanofibers as a copper electrode seal for short-circuit failure inhibition - Chenyang Li; Hitomi Yagyu; Shun Ishioka; Takaaki Kasuga; Hirotaka Koga; Masaya Nogi (Carbohydrate Polymer Technologies and Applications)
Short-circuit failure caused by water or moisture should be avoided in electronic devices. Traditionally, electrodes are sealed with epoxy resin to prevent failure. We previously reported that sealing copper electrodes with sodium-type 2,2,6,6-tetramethylpiperidine-1-oxyl (TEMPO)-oxidized cellulose nanofibers (TOCNs) inhibited failure. Sodium carboxylate groups in TOCNs are counterion-exchangeable, and then ion exchange in TOCNs changes their properties, such as hydrophilicity, and oxygen permeability. In this study, we evaluated the properties of different ion-exchanged TOCNs as copper electrode seals. TOCN ion-exchanged with lithium carboxyl groups (TOCN–Li) showed equivalent water swelling ability with TOCNs with sodium carboxylate groups (TOCN–Na). Therefore, the TOCN–Li-sealed electrodes successfully prevented short circuit, as long as the TOCN–Na. Moreover, TOCN–Li layers have low coefficient of thermal expansion that limits the thermal exfoliation of the substrates, high adhesion strength that prevents physical peeling from substrates, and self-extinguishing, inhibits burning. These findings are expected to accelerate the development of sustainable electronic devices.